Status of Engineering College Libraries in Ambala District of Haryana:A Survey - Partap, Bhanu (Journal of Information and Knowledge, 2016)
The present study is an evaluative survey based study of current status of libraries of engineering colleges located in Ambala District of Haryana affiliated to KurukshetraUniversity, Kurukshetra and MaharishiMarkandeshwarUniversity, Mullana, Ambala. This study attempts to evaluate the three broad aspects, i.e. staff, collection and services. In addition, state of Information and Communication Technology (ICT) infrastructure and use of applications of information technology in respect of its housekeeping activities as well as for user services, print and electronic resources, collection development policies, computerized services, Internet facilities, technical activities, etc. based on questionnaire survey. Thirteen questionnaires were distributed to the librarians of the colleges, out of which ten responses were received. Based on the result of the survey and major findings, few suggestions have been given. This result can conclude that the colleges need to strengthen their libraries, in terms of staff positions, buildings, collection development policy, salary structure to the professionals, so as to achieve the objectives and goals of providing effective library services to its users in an automated environment.